Histopathological Changes in Liver Induced by Piroxicam Administration in Adult Male Albino Mice Mus musculus - Intidhar Mohammed Mnati1 , Baydaa Hussain Mutlak1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Piroxicam is one of non-steroidal anti-inflammatory drugs which is widely used in treating rheumatic disorder. Aim of the study: Studying the effects of piroxicam pertaining on the liver tissue to the chronic administration in male albino mice Mus musculus histologically and histochemically changes. Material and methods: A total number of (30) adult male albino mice were utilized in this study, they were randomly distributed into three groups, the first and second groups were orally treated with concentrations (75, 150) mg/kg of piroxicam respectively for one and two months, the third group considered as control group were orally treated with distilled water, liver samples were collected every one and two months for the histological and histochemically study. Results: This study recorded the presence of histopathological changes in liver tissue of the treated mice with concentration 75 mg/kg represented by degeneration of hepatocyte, sinusoidal dilation, inflammatory cellular infiltration, vascular congestion in the portal vein and beginning of calcium casts formation, while the group treated with 150 mg/kg of the drug showed portal vein congestion and dilation, blood sinusoidal were highly obliterated, proliferation of bile duct and nuclei appeared pyknotic, in addition there were a remarkable decrease in the glycogen controls of cells. Conclusion: It could be concluded that piroxicam drugs has drastic effects on liver tissue as represented by the observed histopathological changes.